Identifying trauma, supporting well-being : the experiences of seven early childhood teachers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education (Special Education) at Massey University, Palmerston North, New Zealand - Isaacs, Cheryl (Massey University, 2006)
This qualitative thesis records the experiences of seven early childhood teachers in identifying trauma and supporting the well-being of children in their care. The teachers, all women, had taught in a range of services including community centres, daycares and kindergartens. They were interviewed separately and their narratives examined using Bronfenbrenner's ecological model, with special attention given to the major macrosystem influence of the principles of the early childhood curriculum, Te Whāriki. The teachers' own personal and professional experiences contributed to their acceptance and knowledge of trauma. Assessment of well-being included observation of children's behaviours, interactions with children and consultation with parents and others, team work, a variety of strategies and individual reflection on practice and personal experiences. The study concludes by debating the usefulness of the trauma label and recommending better promotion and access to information and support for teachers and families on the aetiology, symptoms and healing of trauma. Attention is also drawn to the complex task of balancing the requirements of children and their families, the difficulties of accessing personal support and the contribution of the ecological model.
Keywords: Psychic trauma in children; Problem children -- Education (Preschool)